Manajemen Konflik dalam Pendidikan : Strategi untuk Menciptakan Suasana Belajar yang Harmonis - Mochammad Fatur Rahman; Mualip Mualip; Alya Rahmawati; Muhammad Farhan Firdaus; Mu’allimin Mu’allimin (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Conflict Management in Education: Strategies to Create a Harmonious Learning Environment" discusses the importance of conflict management in creating a conducive and productive learning environment. Conflict is a natural part of the educational environment, but if not managed properly, it can disrupt the teaching and learning process and damage relationships between individuals. Conflict can arise from various sources, such as differences of opinion, competition, lack of communication, limited resources, and inappropriate behavior. This article emphasizes the importance of effective conflict management as the key to creating a harmonious atmosphere in schools, by outlining proactive and holistic strategies, including conflict prevention, conflict resolution, and building a harmonious atmosphere. This article aims to identify, analyze, and synthesize various sources of literature relevant to the topic of conflict management in education, as well as provide an in-depth understanding of strategies in resolving conflicts to create a harmonious atmosphere.